Pengaruh norma subjektif dan need for achievement terhadap intensi berwirausaha mahasiswa - Yulistiani Telaumbanua; Sri Arita (Universitas Negeri Surabaya, 2025)
The low interest in entrepreneurship among students contributes to the high rate of educated unemployment in Indonesia. The high rate of educated unemployment in Indonesia necessitatesan increase in entrepreneurial intention among students. This study aims to analyze the influence of subjective norms and need for achievement on students entrepreneurial intention The method used is descriptive associative, and data were obtained thru the distribution of questionnaires to 308 randomly selected students. The results of this study indicate that subjective norms and the need for archievement significantly influence entrepreneurial intention. This finding confirms that social support from the surrounding environment and the drive to achieve are important factors in shaping students intention to start a business.